Simulasi Jaringan Komputer Dengan Routing Dinamic Menggunakan Cisco Packet Tracer - Indra Maulana (Sekolah Tinggi Ilmu Komputer YOS SUDARSO Purwokerto, 2021)
The need for computer network information is very important, especially for finding network damage quickly, easily, and cheaply, so to solve the above problem a network administrator needs a Network Monitoring System application for simulations that can reflect the architecture of the computer network on the network system used. By using the Cisco Packet Tracer application, data simulation about the network can be used as information about the state of a computer connection in a network, if there is a problem in network interconnection. Based on the results of delay testing according to Cisco Packet Tracer software, the greatest delay results occur when testing Floor 1 to floor 2, and in Design, which is 254 ms. Thus the greater the delay that occurs, the greater the delay time required to transmit data packets. Testing on the test network simulation design in this thesis has been successful, where 3 routers and 6 clients on the network can communicate on the local network that has been simulated.